Transformation of islamic educational institutions in realizing quality human resources in the global era - Amet Amet (Enrichment : Journal of Management, 2023)
In the current era of information openness and transformation, Islamic educational institutions must formulate the right strategy, keep abreast of developments in people's lives, provide the best service needed by the community, create breakthroughs, innovation and endless creativity so that the graduates have reliable quality human resources, obtain various skills and expertise in accordance with the developments and demands of the global era based on strong and deep-rooted faith and Islam and being able to integrate basic Islamic values with the noble culture of the Indonesian nation. Transformation of Islamic Education is an attempt to make adjustments to the implementation of Islamic education from a religious-based Islamic education model such as the model of madrasah and Islamic boarding schools to a model of general education and/or other designations based on Islamic values. This adjustment of Islamic education institutions is not to replace the madrasah and pesantren models but to provide a variety of choices to the community for the needs of Islamic education services according to their social situations and conditions.